2017
DOI: 10.1371/journal.pone.0180281
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of CXCR3 chemokine during organizing pneumonia on the risk of chronic lung allograft dysfunction after lung transplantation

Abstract: RationaleSince the pathogenesis of chronic lung allograft dysfunction (CLAD) remains poorly defined with no known effective therapies, the identification and study of key events which increase CLAD risk is a critical step towards improving outcomes. We hypothesized that bronchoalveolar lavage fluid (BALF) CXCR3 ligand concentrations would be augmented during organizing pneumonia (OP) and that episodes of OP with marked chemokine elevations would be associated with significantly higher CLAD risk.MethodsAll tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…Attempts were made to identify markers from BAL fluid to detect allograft rejection [ 12 ]; however, no marker has been identified that has the predictive power [ 13 ]. From previous studies, a pro-inflammatory cytokine—CXCL10—in BAL was reported to be associated with the risk factor of CLAD development [ 14 ]. A study by Yang et al reported using cfDNA and CXCL10 derived from BAL to detect and distinguish subphenotypes of CLAD and to predict lung transplant survival [ 15 ].…”
mentioning
confidence: 99%
“…Attempts were made to identify markers from BAL fluid to detect allograft rejection [ 12 ]; however, no marker has been identified that has the predictive power [ 13 ]. From previous studies, a pro-inflammatory cytokine—CXCL10—in BAL was reported to be associated with the risk factor of CLAD development [ 14 ]. A study by Yang et al reported using cfDNA and CXCL10 derived from BAL to detect and distinguish subphenotypes of CLAD and to predict lung transplant survival [ 15 ].…”
mentioning
confidence: 99%
“…149 As previously noted, the major risk factor for RAS is DAD, 114,115 and possibly OP as well. 130 Thus, we infer that BOS is preceded by injury to the small airways, whereas RAS follows an injury that may involve the small airways as well, but also extends distally to the alveoli.…”
Section: Mechanisms Of Clad Pathogenesis Injury and Dysregulated Repamentioning
confidence: 83%
“…115 Furthermore, BAL fluid concentrations of these chemokines are increased during injury, and the levels associate with the subsequent development of CLAD. 115,[128][129][130] CXCR3 chemokine ligands are also increased during community-acquired respiratory viral infection, and high levels predicted worse allograft function 6 months after recovery from the infection. 131 These studies suggest that CXCR3/ligand biology during allograft injury may set up the scenario for progression to CLAD by recruiting cytotoxic lymphocytes to the graft.…”
Section: Mechanisms Of Clad Pathogenesis Injury and Dysregulated Repamentioning
confidence: 99%
“…This finding is corroborated by previous work showing that protein concentrations of the interferon gamma–inducible CXCR3-binding chemokines in the BAL fluid are associated with A-grade ACR and other lung injury patterns, as well as with CLAD. 25 , 26 , 27 Finally, enrichment for pathways related to cell adhesion, NK cell–mediated cytotoxicity, and allograft rejection add additional support of the biological relevance of BAL CP gene expression during A-grade ACR.…”
Section: Discussionmentioning
confidence: 94%